Evidence Brief: Supporting Optimal Screening Approaches in Canada - Wilson, MG; Lavis, JN (My University, 2013)
An assessment of what is known about problems related to optimal screening approaches, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stake holder dialogue on the topic of supporting optimal screening approaches in Canada.
Keywords: screening; Canada